The Construction of Turkish Identity with The Success of Turkish Origin Scientists during COVID-19 Pandemic - Emel Özdemir (Selçuk İletişim)
It is aimed to make out how the media that reshapes the societies with the discourses affects the construction of Turkish identity that is influenced by the Turkish origin scientists’ worldwide success about coronavirus pandemic. By studying the news and images, it is purposed to analyze whether the otherization of Turkey that is generally established with different kinds of many bad images, expressions from past to now is still keeping alive with all the images, discourses, expressions in the media. It is aimed to analyze if there is a different point of view in Germany with successful Turkish origin scientists who are being hope for all the world in the process of coronavirus pandemic. The aim of this study is to demonstrate how Turkey is described after the contribution of the Turkish origin scientists to the world about coronavirus, by examinig the news about Turkey in Der Spiegel International (Germany) throughout four months (October, November, December in 2020 and January in 2021) with using the discourse analysis method.